Social Media Marketing Strategy Analysis and Implementation to Increase Customer Engagement (Case Study at PT. XYZ) - Della Hernita Putri; Sfenrianto Sfenrianto (UniSadhuGuna Business School, 2023)
social media plays a significant part in marketing promotion techniques in the modern, digitalized corporate world. Because of its rapid growth, it is important to note social media's influence on marketing for both small and large businesses, using social media as a marketing tool necessitates the owner to develop customer connection with their follower(s) or member(s). Posting content to social media must have a clear concept and strategy to be successful, not only for promoting the business but also it can increase sales and dig up more information about their follower(s) by doing various kind of interactions and activities. This study attempted to investigate and explore the impact of Social Media Marketing Strategy Analysis and Implementation to increase Customer Engagement at PT.XYZ. This study uses a social media marketing strategy framework by Tuten & Solomon, and a qualitative method which data collection is done by interview and observation. The result showed that with maximizing the features and applying the concept social media marketing strategy, can increase the customer engagement and in the sales conversions as well